2019
DOI: 10.1038/s41598-019-45421-7
|View full text |Cite
|
Sign up to set email alerts
|

A genetically encoded fluorescent temperature sensor derived from the photoactive Orange Carotenoid Protein

Abstract: The heterogeneity of metabolic reactions leads to a non-uniform distribution of temperature in different parts of the living cell. The demand to study normal functioning and pathological abnormalities of cellular processes requires the development of new visualization methods. Previously, we have shown that the 35-kDa photoswitchable Orange Carotenoid Protein (OCP) has a strong temperature dependency of photoconversion rates, and its tertiary structure undergoes significant structural rearrangements upon photo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 40 publications
(52 reference statements)
0
25
0
Order By: Relevance
“…Finally, it has recently been demonstrated that OCP can quench different fluorescent energy donors via fluorescence resonance energy transfer [74,75], suggesting that OCP can be used as a regulator of fluorescence in light, temperature, and other types of sensors (see Outstanding Questions). was financed by the European Union's Horizon 2020 (project SE2B).…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%
“…Finally, it has recently been demonstrated that OCP can quench different fluorescent energy donors via fluorescence resonance energy transfer [74,75], suggesting that OCP can be used as a regulator of fluorescence in light, temperature, and other types of sensors (see Outstanding Questions). was financed by the European Union's Horizon 2020 (project SE2B).…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%
“…This question is related to the fact that the differences between the environment of ECN in the dimeric AnaCTDH holoprotein and in the membrane are significant ( Figure A1 ), so the transition of carotenoid between these states requires consideration of intermediate protein-carotenoid-membrane complexes. In an attempt to detect such complexes experimentally, we designed a chimeric protein by fusing AnaCTDH and a red-fluorescent protein (TagRFP) according to procedures described in [ 49 ]. In such a chimera, TagRFP serves as a fluorescent reporter, the quantum yield of which is sensitive to the presence of the carotenoid in AnaCTDH.…”
Section: Spectroscopic Characterization Of the Anactdh Apoprotein Spementioning
confidence: 99%
“…In such a way, OCP R prevents the overexcitation of the photosynthetic reaction centers and efficiently suppresses the photodamage of the photosynthetic apparatus. Under in vitro conditions in the absence of PBS, OCP R spontaneously back-converts into OCP O in the dark, which is strictly dependent on temperature 11 , 12 , 20 . Termination of the OCP-dependent PBS fluorescence quenching in vivo is usually promoted by the Fluorescence Recovery Protein (FRP), which forces detachment of OCP R from PBS and promotes relaxation of OCP R back to OCP O 18 , 21 23 .…”
Section: Introductionmentioning
confidence: 99%
“…Such red forms with separated protein domains are capable of inducing PBS fluorescence quenching without prior light activation 21 . However, many other amino acid substitutions lead to the same result due to destabilization of carotenoid-binding abilities of OCP, which increases conformational and thus spectral heterogeneity of the sample 20 , 45 , 46 . Spectral heterogeneity can also be increased due to the embedment of different carotenoids into OCP 47 .…”
Section: Introductionmentioning
confidence: 99%